Overhead in multicast - Rigotti, Guillermo (1999)
A class of multicast applications, such as reliable multicast, consists of a sender and a set of receivers sending feedback information to the sender and the rest of the receivers. If multicast support is based on source based trees, the above feature can cause an excessive overhead, specially when number of receivers increases (in the order of thousands) The reason is the need to maintain a distribution tree per receiver. This paper presents an extended use of source based frees. It enables distribution of information originated by members of the group through the tree rooted at the sender. This aims to reduce the amount of memory in routers as a consequence of maintaining only one distribution tree per application.